Across ancestries, HLA-B∗08:01∼DRB1∗03:01 (DR3) and HLA-DQA∗01:02 (DR2) increase the risk to develop juvenile-onset systemic lupus erythematosus through low complement C4 levels - Yves Renaudineau; Amandine Charras; Valentina Natoli; Nicolas Congy-Jolivet; Sam Haldenby; Xuan Liu; Yongxiang Fang; Eve MD. Smith; Michael W. Beresford; Christian M. Hedrich; Carla Roberts; Eslam Al-Abadi; et al. (Journal of Translational Autoimmunity)
Objective: Systemic lupus erythematosus (SLE) is a systemic autoimmune/inflammatory disease with a strong genetic component. Genetic burden is higher in children when compared to patients with adult-onset SLE, contributing to earlier disease expression and more severe phenotypes. The human leukocyte antigen (HLA) cluster on chromosome 6p21.3 is among the most variable genomic regions, representing a major risk-factor for SLE in adults. Its impact on juvenile-onset (j)SLE remains largely unstudied. Methods: High-resolution sequencing of HLA class I (A, B, C), class II (DRB1, DQA1, DQB1) and class III (complement C2) was undertaken in the multi-ancestral UK JSLE Cohort including participants of Caucasian (n = 151, 48.8 %), Asian (n = 108, 35.0 %) and African/Caribbean (n = 50, 16.2 %) descent. Considering ancestral variation, clinical associations were tested at the level of alleles (2-field resolution), associated HLA protein sequences (antigen binding domains, 4-field resolution), and extended haplotypes (DRh). Results: Although important ancestral recombination was reported for HLA-DR2 and -DR3 haplotypes, risk associated with jSLE was conserved at related alleles (DR2h: DRB1∗15:01, DQA∗01:02, DQB1∗06:02; DR3h: C∗07:02 [Asian], B∗08:01, C2 rs9332730 [Asian], DRB1∗03:01). HLA-DR7 haplotypes (DRB1∗07:01, OR = 0.44, 95 % CI:0.27–0.72, p = 0.0004; DQA1∗02:01, OR = 0.34, 95 % CI:0.21–0.56, p = 1.8 × 10−6) protect Asians from jSLE development. Among 23 clinical variables recorded, the main association was found between low levels of complement C4 in Caucasian carriers of HLA-DR3h. This was not the case in Asians due to recombination with HLA-C∗07:02 and integration of the C2 rs9332730 minor allele. Low C4 serum levels associated with HLA-DQA1∗01:02 (DR2h) in Caucasians after excluding HLA-DR3h carriers from the analysis. An association between low white blood cell counts and HLA-A∗03:01P was observed across ancestries. Conclusion: Genetic variation in the HLA cluster associates with organ domain involvement (hematological) and complement levels in jSLE. Lupus-associated HLA haplotypes vary between ancestral groups, underscoring the importance of multi-ancestral approaches to genetic studies in SLE and other autoimmune/inflammatory diseases.